FACTORS INFLUENCING BURDEN OF CAREGIVERS OF CHILDREN WITH ADHD DURING COVID-19 PANDEMIC - Damsri, Jaratsri; Nintachan, Patcharin; Sangon, Sopin (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2024)
This predictive correlational research aimed to investigate: 1) the relationships between the worry about the COVID-19 pandemic, resilience, caregiver-perceived severity of ADHD, and number of comorbidities, and the burden of caregivers of children with ADHD; and 2) the predictive ability of these factors on caregiver burden during the COVID-19 pandemic. The participants were 204 caregivers of children with ADHD who sought services at the outpatient clinic of a tertiary hospital in Bangkok. The research tools consisted of the caregiver burden scale, the worry about COVID-19 scale, the resilience inventory, and the SNAP-IV. The Cronbach’s alpha coefficients of the research instrument were .93, .93, .93 and .94, respectively. Data were analyzed using descriptive statistics, Pearson’s product-moment correlation coefficients, Spearman’s rank correlation coefficients, and hierarchical multiple regression analysis. The findings revealed that 34.8 percent of caregivers of children with ADHD had moderate to high levels of caregiver burden. The worry about the COVID-19 pandemic and the perceived severity of ADHD were positively and significantly associated with caregiver burden, while resilience was negatively and significantly related to caregiver burden. The worry the COVID-19 pandemic, caregiver-perceived severity of ADHD, resilience, and the number of comorbidities collectively explained 27.6% of the variance in caregiver burden, with statistical significance. The worry about the COVID-19 pandemic had the greatest impact on caregiver burden (Beta = .310, p = .000), followed by caregiver-perceived severity of ADHD (Beta = .300, p = .000) and resilience (Beta = -.192, p = .002). However, the number of comorbidities was not significantly correlated with caregiver burden (r = .133, p > .05) and did not significantly affect caregiver burden (Beta = .108, p > .05). The results of this study could serve as foundational data for developing guidelines to prevent or reduce caregiver burden among those caring for children with ADHD.